JEJAK BETON DAN MODERNISASI ARSITEKTUR DALAM PEMBANGUNAN PERIODE PASCAKOLONIAL DI INDONESIA - Nia Namirah Hanum; Hanifa Fijriah Wasnadi (ITB Ahmad Dahlan Jakarta, 2021)
1959 was a turning point for Indonesia to become a country with a new 'identity', where it was the first year of the revival of the 1945 Constitution, including the actions, decisions, and powers of the President to initiate large-scale development. For President Soekarno, concrete was able to become a tool to symbolize modernity and equality for the Indonesian people who experienced long imperialism from the Europeans (colonies). Indonesia's long history triggered Soekarno to make Indonesia an equal country with other countries, so through the Nation and Character Building mission, megaprojects were carried out. While the next era is in the hands of President Soeharto, national stability which refers to the development of basic needs and infrastructure is one of the important plans in the PELITA program series. How was the modernization process in Indonesia in the post-colonial period presented through concrete materials and what factors or events were related to it; become the focus of the problem in this research. The purpose of exploring these problems is to get a new perspective to explore and assess the role of concrete in the Indonesian modernization process in physical development which was influenced by important factors and events in the two postcolonial regimes. The data on domestic cement production and consumption activities in Indonesia serve as glasses to see how the traces of the modernization of the Indonesian nation are in the context of physical development. The results show that there are two peaks of the highest domestic consumption of cement which proves that concrete is an important part of the development process in the post-colonial period: (1) In 1961 it was 788,000 tons in the era of the construction of the Istiqlal Mosque, an increase of 73.6% from the previous year; (2) In 1970, it reached 1,214,603 tons in the PELITA I era, with an increase of 27% from the previous year.